Effect of using phase change material (PCM) magnesium sulfate (MgSO4) solution as heat storage in solar powered thermoelectric cooler box - Priyuko, D.; Rifky, R.; Saputra, A.; Fahrezi, A.I.; Sobirin, M.I. (Universitas Mataram, 2025)
Utilization of new, renewable energy sources is very important for society as a way to switch from fossil fuels. Solar energy is a type of renewable energy that is very promising for various applications. Traditional cooling systems contribute to the depletion of the ozone layer, requiring alternatives such as using thermoelectric solar energy (TEC) for cooling. In addition, PCM used, such as 25%, 30%, and 35% MgSO₄ solutions, can absorb latent heat during the cooling process, thereby increasing efficiency. This research aims to increase coefficient of performance (CoP) of cooling boxes by integrating solar energy and PCM. Data collection was carried out from 09.30 to 14.40, by measuring light intensity, voltage and current, solar panel temperature, environmental temperature, cooler box wall temperature and TEC temperature. Over three days of data collection, this study determined the minimum temperature and CoP for the cooler. The findings show that the minimum temperature in the cooler without PCM is 16.8℃. Coolers with PCM MgSO₄, 25%, 30%, and 35% the minimum temperatures are 16.7℃, 12.7℃, and 14.7℃. Regarding the average COP, the cooling box without PCM reached 0.0345, while the box with 25%, 30%, and 35% PCM MgSO₄ had a CoP of 0.0354, 0.0469, and 0.0402, respectively. The study concluded that 30% MgSO₄ PCM solution is most suitable for use as PCM, because it affects the minimum temperature and COP of the cooling system. This effectiveness is due to the concentration of MgSO₄ lowering the freezing point of the solution, thereby increasing the cooling performance.